Cancer's toughest challenges: a new call to the physical sciences. (12th October 2017) - Scott, David
Abstract: In 2015, Cancer Research UK's Grand Challenge scheme called on the global scientific community to join forces to tackle the most intractable problems in cancer. Here, we reflect on how the global scientific community came together and shared the outcomes of round one: funding of four international teams with awards totalling £70 million. These new collaborations mark the beginning of what we hope will be a growing international, multidisciplinary Grand Challenge community. The latest Grand Challenge call is now open and we again encourage scientists from any discipline, anywhere in the world, to apply.